The Role of the Plasma Membrane H+-ATPase in Plant Responses to Aluminum Toxicity - Zhang, Jiarong; Wei, Jian; Li, Dongxu; Kong, Xiangying; Rengel, Zed; Chen, Limei; Yang, Ye; Cui, Xiuming; Chen, Qi (Frontiers in Plant Science, 2017)
Aluminium (Al) toxicity is a key factor limiting plant growth and crop production on acid soils. Helping plants cope with Al toxicity by increasing the Al-detoxification capacity and/or breeding Al-resistant cultivars is a cost-effective strategy to mitigate the problem. Plasma membrane H+-ATPase plays a central role in all plant physiological processes. Changes in the activity of the plasma membrane H+-ATPase through regulating the expression and phosphorylation of this enzyme are also involved in many plant responses to Al toxicity. The plasma membrane H+-ATPase mediated H+ influx may be associated with the general maintenance of cytosolic pH and the plasma membrane gradients as well as Al-induced citrate efflux mediated by a H+-ATPase coupled MATE co-transport system. In particular, modulating the activity of plasma membrane H+-ATPase through application of its activators (eg. magnesium or IAA) or using transgenics can effectively enhance plant resistance to Al stress in several species. In this review, we critically assess the available knowledge on the role of the plasma membrane H+-ATPase in plant responses to Al stress, incorporating physiological and molecular aspects.